Microalgal extracts induce larval programming and modify growth and the immune response to bioactive treatments and LCDV in Senegalese sole post-larvae. Issue 106 (November 2020) - Carballo, Carlos; Mateus, Ana Patricia; Maya, Claudia; Mantecón, Lalia; Power, Deborah M.; Manchado, Manuel
Abstract: Immunostimulants are key molecules in aquaculture since they heighten defensive responses and protection against pathogens. The present study investigated the treatment of Senegalese sole larvae with a whole-cell crude extract of the microalgae Nannochloropsis gaditana (Nanno) and programming of growth and the immune system. Larvae at hatch were treated with the Nanno extracts for 2 h and thereafter were cultivated for 32 days post-hatch (dph) in parallel with an untreated control group (CN). Dry weight and length at 21 days post-hatch (dph) were higher in post-larvae of the Nanno than CN group. These differences in weight were later confirmed at 32 dph. To evaluate changes in the immune response associated with Nanno-programming treatments, the Nanno and CN post-larvae were supplied with two bioactive compounds yeast β-glucan (Y) and a microalga extract from the diatom Phaeodactylum tricornutum (MAe). The bioactive treatments were administrated to the treatment groups through the live prey (artemia metanauplii, 200 artemia mL −1 ) enriched for 30 min with MAe or Y (at 2 mg mL −1 SW) or untreated prey in the case of the negative control (SW). The effect of the treatments was assessed by monitoring gene expression, enzyme activity and mortality over 48 h. The post-larvae sole supplied with the bioactive compounds Y and MAe had increased mortality at 48 h compared to the SW group. Moreover, mortality was higher in Nanno-programmed than CN post-larvae. Lysozyme and total anti-protease enzymatic activities at 6 and 24 h after the start of the trial were significantly higher in the Nanno and MAe supplied post-larvae compared to their corresponding control (CN and SW, respectively). Immune gene transcripts revealed that il1b, cxc10 and mx mRNAs were significantly different between Nanno and CN post-larvae at 6 and 24 h. Moreover, the expression of il1b, tnfa, cxc10, irf3, irf7 and mx was modified by bioactive treatments but with temporal differences. At 48 h after bioactive treatments, Y and SW post-larvae were challenged with the lymphocystis disease virus (LCDV). No difference existed in viral copy number between programming or bioactive treatment groups at 3, 6 and 24 h after LCDV challenge although the total number of copies reduced with time. Gene expression profiles in the LCDV-challenged group indicated that post-larvae triggered a wide defensive response compared to SWC 24 h after challenge, which was modulated by programming and bioactive compound treatments. Cluster analysis of expressed genes separated the SW and Y groups indicating long-lasting effects of yeast β-glucan treatment in larvae. A noteworthy interaction between Nanno-programming and Y-treatment on the regulation of antiviral genes was observed. Overall, the data demonstrate the capacity of microalgal crude extracts to modify sole larval plasticity with long-term effects on larval growth and the immune responses. Highlights: Crude extracts of microalga Nannochloropsis gaditana modified larval programming for growth performance in sole post-larvae. Yeast β-glucan and microalgal extract activated immune gene responses but modulated by larval programming in sole post-larvae. LCDV DNA copies were not modified by programming or bioactive treatments. LCDV activated a wide defensive response modulated by yeast β-glucan and Nanno-programming.